2019
DOI: 10.2147/cmar.s193921
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Cadherin-11</em> is inactivated due to promoter methylation and functions in colorectal cancer as a tumour suppressor</p>

Abstract: Background: The cadherin-11 ( CDH11 , OB-cadherin) gene is a member of the cadherin family and is located on chromosome 16q22.1. Previous studies have revealed that cadherins play significant roles in the development of many human malignancies. Increasing evidence has identified CDH11 as a functional tumour suppressor, which is commonly silenced by promoter methylation, but the functions of this gene in colorectal cancer (CRC) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The CDH11 gene, located in the 16q22.1 region and belonging to the E-cadherin family, is often involved in an important group of cell-cell adhesion molecules that mediate intercellular adhesion by Ca 2+dependent hemophilic interactions [13] . Because cadherins have been widely documented in cancer development [14] , the promoter CpG island hypermethylation-associated silencing of the CDH11 gene, a component of this superfamily, is consistent with the hypothesis that epigenetic inactivation of this gene could be involved in the tumorigenesis and progression of carcinomas. L Li et al [15] found that the CDH11 gene is frequently methylated in a variety of tumor tissues including esophageal squamous cell carcinoma (13/14, 93%), nasopharyngeal carcinoma (17/18, 94%), hepatocellular carcinoma (28/42, 66%), breast carcinoma (11/12, 91%), gastric carcinoma (13/13, 100%), colon carcinoma (10/11, 90%) and other carcinomas.…”
Section: Introductionsupporting
confidence: 77%
“…The CDH11 gene, located in the 16q22.1 region and belonging to the E-cadherin family, is often involved in an important group of cell-cell adhesion molecules that mediate intercellular adhesion by Ca 2+dependent hemophilic interactions [13] . Because cadherins have been widely documented in cancer development [14] , the promoter CpG island hypermethylation-associated silencing of the CDH11 gene, a component of this superfamily, is consistent with the hypothesis that epigenetic inactivation of this gene could be involved in the tumorigenesis and progression of carcinomas. L Li et al [15] found that the CDH11 gene is frequently methylated in a variety of tumor tissues including esophageal squamous cell carcinoma (13/14, 93%), nasopharyngeal carcinoma (17/18, 94%), hepatocellular carcinoma (28/42, 66%), breast carcinoma (11/12, 91%), gastric carcinoma (13/13, 100%), colon carcinoma (10/11, 90%) and other carcinomas.…”
Section: Introductionsupporting
confidence: 77%
“…Cadherin-11 (CDH11) is an adhesion protein mainly expressed in mesenchymal tissues that regulates the differentiation and function of osteoblasts. CDH11 was identified to participate in multiple BPs including bone formation, cellular signal transduction, tumor invasion, and metastasis (Lee et al, 2007;Li et al, 2012;Langhe et al, 2016;Madarampalli et al, 2019;Yuan et al, 2019a), and also play important roles in developmental and pathogenic mechanisms of heart valve (Zhou et al, 2013;Bowler et al, 2018). A recent study found that CDH11 contributed to inflammation-driven fibrotic remodeling after myocardial infarction (Schroer et al, 2019), which indicated that the increased CDH11 might be involved in the development of HF through inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sepulveda et al [36] found that CDH11 had signi cantly increased CpG methylation and decreased expression in gastric cancer. CDH11 was also downregulated in colorectal cancer due to its promoter methylation, which was linked to cell cycle arrest in the G0/G1 phase and apoptosis [37] . Furthermore, the methylation-induced regulation of CDH11 has been found in many other cancers, such as melanoma and bladder cancer [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%